Dates and Diabetes - Chaudhary, Sandeep; Pankaj, Aswin (Journal of Social Health and Diabetes, 2018)
Date, the fruit of date palm, is a delicious fruit with a sweet taste and a fleshy mouth feel. Dates have been considered as the staple food in the Arab Gulf regions for thousands of years. The religious-cultural importance of this fruit often creates conflict between persons with diabetes, who wish to consume it in unlimited quantity, and health care professionals, who condemn its consumption. This article provides a balanced, nutrilogic opinion about dates and their consumption in diabetes.
Keywords: Arab diabetes; diabetes; glycemic index; glycemic load; medical nutrition therapy